A bibliometric visualization of resistance to lung cancer immunotherapy: a decade of research progress (2014–2024) - Yang, Zhuo; Yang, Lanlan; Wang, Yuli; Ren, Xiangyu; Cui, Yajing; Li, Yan; Wu, Jianchun (Frontiers in Oncology, 2025)
BackgroundLung cancer remains the leading cause of cancer-related deaths globally and represents the most common malignant tumor. While immunotherapy has significantly improved patient survival in recent years, the development of resistance limits its clinical efficacy. Currently, a systematic and comprehensive bibliometric analysis of drug resistance in immunotherapy for lung cancer is lacking. This study aims to address this gap by employing bibliometric methods to illuminate the knowledge structure and to identify key research hotspots in this critical area.MethodsWe retrieved publications concerning lung cancer immunotherapy drug resistance from the Web of Science Core Collection and PubMed databases, covering January 1, 2014, to December 31, 2024. NoteExpress was used for data integration, duplicate detection, and screening. Subsequently, we quantitatively and visually analyzed the characteristics of the selected literature, with an emphasis on country, institution, and keywords. This analysis was performed utilizing VOSviewer, CiteSpace, and the “bibliometrix” package in R.ResultThe annual publication output showed a marked upward trend, peaking in 2024. China produced the most publications, while the USA demonstrated higher citation impact. Analysis of keywords revealed a clear thematic evolution: from initial focus on clinical trials (e.g. Open-label) and specific drugs (e.g. Nivolumab), to immune checkpoints (e.g.PD-1/PD-L1), and more recently to underlying molecular mechanisms like the tumor microenvironment, autophagy, and ferroptosis.ConclusionsThis study offers a thorough overview of the most important research topics and emerging trends related to drug resistance and lung cancer immunotherapy. By integrating current knowledge, it enables researchers to swiftly identify pivotal research directions, thereby promoting in-depth development and innovation within the field and supporting the progression of clinical practice. For clinicians, this bibliometric insight provides a more scientific and precise basis for formulating treatment strategies, ultimately assisting lung cancer patients in deriving benefits from immunotherapy.